CYBER SECURITY IN THAILAND: A MISSION TOWARDS SAFETY IN THE DIGITAL AGE - Poonsawat, Thipphawan (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This article aims to examine the development and implementation of cybersecurity measures in Thailand, focusing on the creation of cybersecurity frameworks, national policies, and strategic guidelines. Method: The study employs a qualitative descriptive approach using secondary data from government documents, legal frameworks, and cybersecurity policy analyses. Results: The findings reveal that Thailand has taken significant steps toward enhancing cybersecurity through legislative measures on personal data protection, public awareness campaigns on cyber threats, and the establishment of specialized cybersecurity agencies. Moreover, Thailand has collaborated with international partners to strengthen its cybersecurity infrastructure, thereby fostering public and institutional trust in digital services and enhancing national security. Novelty: This study contributes a comprehensive overview of Thailand’s cybersecurity evolution, emphasizing not only the importance of legal and institutional mechanisms but also the strategic role of public engagement and international cooperation. The article offers practical guidelines for further strengthening cybersecurity systems in Thailand to align with global standards and addresses key challenges in achieving robust digital security across sectors.